Características de codornas japonesas provenientes de ovos incubados em diferentes temperaturas - Souza, Alexandre Vinhas de (2021)
The objective of this study was to evaluate the influence of different incubation temperatures (IT) on the post-hatching reproductive characteristics of Japanese quails (Coturnix coturnix japônica). A total of 1332 fertile eggs were incubated at different temperatures: 36.0, 37.5 and 39.0 ° C. After hatching, the birds were transferred to breeding cages until 35 days of age and, later, to production cages in groups of nine females and three males. The experimental design was in randomized blocks (repetition over time) with three treatments and six repetitions, with the experimental unit represented by two cages. IT did not influence (P> 0.05) birth weight and hatching window, however, greater hatchability (P <0.05) was observed in eggs incubated at 37.5 ° C. There was no effect (P> 0.05) of the TI on the relative weight of the organs at 35 and 60 days of age and on the growth curve of the males. In females, body weight at maturity of growth was higher (P <0.01) when the IT was 39.0 ° C. The anatomy of the testicles and semen characteristics were not influenced (P> 0.05) by IT, except for sperm viability, which was higher (P <0.05) when temperatures of 37.5 and 39.0 oC were used. There was no effect (P <0.05) of the IT on the fertility of the eggs and also on the morphological characteristics of the female reproductive organs. However, younger age at the first egg and younger age at which birds reached 80% were observed (P <0.05) when the IT was 39.0 ° C. There was no effect (P> 0.05) of the IT on egg quality, except for the yolk height, which was higher (P <0.01) in the ITs of 36.0 and 39.0 ° C. It is concluded that the temperature of 37.5 ° C should be used during the incubation of Japanese quail eggs.